THE COMPARISON OF CLASSICAL TAFSIR AND CONTEMPORARY INTERPRETATION REGARDING THE VERSES OF ASTROPHYSICS AND COSMOLOGY IN THE QUR’AN - Ansharullah, Azra; Imamuddin, Basuni (UI Scholars Hub, 2025)
As time progressed, various kinds of discoveries in the field of science emerged one by one, especially in the field of Astronomy and its